PREVALENCE OF MALNUTRITION AND ASSOCIATED FACTORS IN ELDERLY HEMODIALYSIS PATIENTS AT THONG NHAT HOSPITAL - Thị Lan Hương, Phạm; Huỳnh Thanh Tuấn, Nguyễn; Minh Tiến, Nguyễn; Bách, Nguyễn (Journal of Health and Aging, 2025)
We conducted this study to determine the prevalence of malnutrition and its associated factors among elderly hemodialysis patients at Thong Nhat Hospital, thereby providing evidence to guide nutritional support and dietary interventions. This cross-sectional, descriptive, retrospective, and comparative study included 158 hemodialysis patients at the Department of Nephrology and Dialysis, Thong Nhat Hospital, Ho Chi Minh City. Participants were divided into two groups: those aged ≥60 years and those aged
Keywords: malnutrition; elderly; hemodialysis; serum albumin; body mass index